Templos no Templo - elementos da pós-modernidade no discurso religioso - Freitas, Johêdyr Adjyan Cartaxo de (2020)
The brazilian population, from the point of view of the profession of religious creed, is composed of a christian majority. However, in the 2010 demographic census, an increase in the number of people who declared themselves to be "without religion" was identified, but contrary to what may seem, this group is averse to religion, but not to spirituality. This is a forms of faith emerging in postmodernity (HALL, 2006; LYOTARD, 2009). This fact indicated the need for an analysis of contemporary religious discourse in a critical way and to understand how it has been communicating with the current public. Place of worship and posts on the internet are texts that through qualitative research, accessibility found the Alive Community and the Adventist Community of Adrianópolis, christian churches of traditionally historical confession provide a historically discontinued religious service. This investigation falls within the dialogue it promotes between Critical Discourse Analysis (FAIRCLOUGH, 2016) with Multimodality (KRESS; van LEEUWEN, 2006), in a contemporary medium of communication: four worship invitations from these churches (which are publicly available on an online social networking platform). After its analysis, it was perceived on the one hand that the churches have used a physical place (shopping center) and a virtual environment (internet) to communicate purposefully with the contemporary public, as it distorts structural and formal aspects; on the other, through the content of these published texts, the use of absolutist terms is noticed, as well as the introduction of expressions that promote affection and informality. This demonstrates that several characteristics of Modernity are present in contemporary religious discourse.